MAKNA KEPENTINGAN UMUM DIDALAM DEPONERING - Windi Jannati M.A.S; Frans Simangunsong (Gapenas Publisher, 2022)
In Law No. 16 of 2004 concerning the Prosecutor's Office, there is a definition or understanding of Deponering namely the public interest, the interest in question is the interest of the state, nation and other community interests as stated in Article 35 (c). This deponering is an implementation of the opportunity principle owned by the prosecutor which has its own purpose, namely adjudicating cases, but the regulations or rules are still unclear, resulting in a blurring of norms because there are no special limits regarding the meaning of the public interest. carried out by the prosecutor and there was a misinterpretation in the determination of deponering. The proposed formulation is as follows 1. What is the meaning of the phrase public interest in deponering based on Article 35 (c) of Law Number 16 of 2004 concerning the Attorney General's Office of the Republic of Indonesia. 2. What are the criteria for public interest as a condition for deponering to realize justice in law enforcement. The research method used is a normative research method using 2 approaches: a statutory approach and a conceptual approach. The results of this study are the meaning of the phrase in question, prioritizing common interests rather than personal interests, and in its application the attorney general must obtain consideration from the state power agency that is related to the problem and the criteria in realizing justice for law enforcement, so in making decisions to using this deponering, the prosecutor must coordinate with the Supreme Court, the constitutional court the DPR, the President